2019
DOI: 10.1093/jnen/nlz005
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Distribution of TDP-43 Pre-inclusions in Primary Progressive Aphasia

Abstract: Diffusely stained phosphorylated 43-kDa TAR DNA-binding protein (TDP-43)-positive "pre-inclusions" have been described. This experiment investigated morphological subtypes of pre-inclusions and their relationship with TDP-43 inclusions in primary progressive aphasia (PPA), a dementia characterized by gradual dissolution of language. Brain sections from 5 PPA participants with postmortem diagnoses of frontotemporal lobar degeneration with TDP-43 pathology (FTLD-TDP) were immunohistochemically stained using an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…An alternative hypothesis is that the same clinically relevant networks are disrupted by different types of neurons, circuits, or regions [ 21 , 88 , 101 , 104 ]. In support of this latter hypothesis, recent investigations by our lab and others have found different regional patterns of peak tau and TDP-43 histopathologic burden within the language network in PPA [ 29 , 27 , 48 , 49 ] and frontotemporal networks in bvFTD [ 43 , 45 ]. FTLD proteinopathies may also display different laminar distributions of pathology in the same clinical syndrome and network, but comparative examinations of tau and TDP-43 pathology in cortical laminae are lacking.…”
Section: Introductionsupporting
confidence: 68%
“…An alternative hypothesis is that the same clinically relevant networks are disrupted by different types of neurons, circuits, or regions [ 21 , 88 , 101 , 104 ]. In support of this latter hypothesis, recent investigations by our lab and others have found different regional patterns of peak tau and TDP-43 histopathologic burden within the language network in PPA [ 29 , 27 , 48 , 49 ] and frontotemporal networks in bvFTD [ 43 , 45 ]. FTLD proteinopathies may also display different laminar distributions of pathology in the same clinical syndrome and network, but comparative examinations of tau and TDP-43 pathology in cortical laminae are lacking.…”
Section: Introductionsupporting
confidence: 68%
“…In addition, our sample set contained a mixture of right and left hemispheres. While some reports found that TDP‐43 in some forms of dementia favors the language‐dominant hemisphere [ 58 , 59 , 60 ], the result has not consistently been replicated [ 48 ], and it is not yet known if it holds true for typical limbic AD. Finally, while we evaluated pathology on the same subfields on adjacent tissue slides, we did not perform double‐staining to assess the co‐localization of pathology at the individual neuron level.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the predominance of one or more of the three types of inclusions, the length of dystrophic neurites, and the laminar distribution of cortical inclusions, TDP‐43 pathology is categorized into subtypes A–E (Lee et al., 2017; Mackenzie et al., 2011). TDP‐43 inclusions appear to be preceded by preinclusions of smooth or granular staining in neurons (Kim et al., 2019).…”
Section: Pathologic Hallmarks Of Neurodegenerative Dementiasmentioning
confidence: 99%